Bengt-Ove Andreassen & James R. Lewis (eds.): Textbook Gods. Genre, Text and Teaching Religious Studies - Trein, Lorenz (Entangled Religions, 2016)
This contribution offers a review of: Bengt-Ove Andreassen & James R. Lewis (eds.): Textbook Gods. Genre, Text and Teaching Religious Studies Sheffield/Bristol: Equinox, 2014. 256 pages, £55.00/85.00 (hardback), £18.99/29.95 (paperback), ISBN: 978-1-78179-054-0 (hardback), ISBN: 978-1-78179-055-7 (paperback).